Educational video for self-care with arteriovenous fistula in renal patients: randomized clinical trial - Natália Ramos Costa Pessoa; Jackeline Kérollen Duarte de Sales; Clemente Neves Sousa; Marcos Venícios de Oliveira Lopes; Cecília Maria Farias de Queiroz Frazão; Vânia Pinheiro Ramos (Universidade de São Paulo, 2024)
Objective: to evaluate the effect of an educational video on the knowledge, attitude, and practice of self-care with arteriovenous fistula in patients undergoing hemodialysis treatment. Method: randomized controlled clinical trial, with two arms and single-blind. The intervention used an educational video on arteriovenous fistula self-care. The Fistula Self-Care Knowledge, Attitude, and Practice Scale was applied to 27 renal patients on hemodialysis in the control group and 28 in the intervention group at baseline, after seven and fourteen days. The data was analyzed using the Statistical Package for the Social Sciences software, using the chi-square test, Student's t-test, Mann-Whitney test, and Friedman's test with post-hoc analysis for multiple comparisons. Results: there were statistically significant differences in the knowledge and practice of self-care with the fistula at 0, 7 and, 14 days in the intervention (p= 0.004 and p<0.001, respectively) and control groups (p<0.001 for knowledge and practice). Attitude showed a significant difference at follow-up (p<0.001), but the post-hoc analysis did not confirm the significance obtained. Conclusion: patients' knowledge and practice showed significant increases at follow-up in the control and intervention groups, while the increase in attitude was not significant in either group. Clinical trial, registration number: U1111-1241-6730.